Развернуто 4(2- 4х) + 6х=3 9х= 5х - (72-2х) 2 (2,5х-1)= -(1,8-4х) 16 умножить (0,25х - 1)= 5 (0,8-3,2) 10х-(2х-4)=4(3х-2)

JuliaPetrova56 JuliaPetrova56    3   08.09.2019 08:50    0

Ответы
rsr rsr  07.10.2020 00:32
1) 8-16х+6х=3
    -16х+6х=3-8
    -10х=-5
    -х=-5:10
    -х=-0,5
     х=0,5
2) 9х=5х-72+2х
    9х-5х-2х=-72
    2х=-72
    х=-72/2
    х=-36
3) 5х-2=-1,8+4х
    5х-4х=-1,8+2
    х=0,2
5) 10х-2х+4=12х-8
     10х-2х-12х=-8-4
      -4х=-12
      -х=-12/4
      -х=-3
       х=3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра